1993
DOI: 10.1007/bf02112027
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of intracranial germ cell tumours: Effectiveness of chemotherapy with cisplatin and etoposide (CDDP and VP-16)

Abstract: A co-operative study for patients with intracranial germ cell tumours was performed to analyze their prognosis and the effectiveness of Cisplatin/Etoposide (CDDP/VP-16) chemotherapy. A total of 46 patients; 30 primary and 16 recurrent cases were registered from 15 participating neurosurgical institutions in Japan. Based on histological criteria and tumour markers, they were classified into three groups; germinoma, germinoma with syncytiotrophoblastic giant cell (STGC), and non-germinomatous malignant tumour. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…Uematsu and other investigators reported that intracranial germinoma with STGC showed a greater tendency to recur than pure germinoma. 42,45 However, Ogawa and other investigators reported that there was no significant difference between the survival of patients with and without STGC. 24,43 It will be important in future studies to evaluate whether these clinical parameters are truly associated with the treatment outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Uematsu and other investigators reported that intracranial germinoma with STGC showed a greater tendency to recur than pure germinoma. 42,45 However, Ogawa and other investigators reported that there was no significant difference between the survival of patients with and without STGC. 24,43 It will be important in future studies to evaluate whether these clinical parameters are truly associated with the treatment outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Studies in new and relapsed patients found responses and/or improved survival after platinum-containing regimens [17][18][19][20][21][22][23][24][25], with one study suggesting synergy with etoposide [26]. Alkylating agents, such as cyclophosphamide (CPM) also were added with apparent efficacy in some trials [12,14,23].…”
Section: Introductionmentioning
confidence: 99%
“…[10] Thereafter, a cisplatin-etoposide combination and carboplatin-etoposide combination were used in the phase II study by the Japanese Intracranial Germ Cell Tumor Study Group. [31] These trials obtained slightly better results in nongerminomatous tumors but failed to obtain any significant benefit.…”
Section: Discussionmentioning
confidence: 99%